Strategi Guru dalam Membentuk Keterampilan Menulis yang Berdampak Positif terhadap Perkembangan Literasi Siswa SMP - Anita Candra Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Writing skills are a crucial component in developing student literacy at the junior high school (SMP) level. Teachers play a strategic role in developing these skills through relevant and impactful pedagogical approaches. This study, a literature review, aims to examine various teacher strategies for developing students' writing skills that positively contribute to their literacy development. Data were collected from various scientific articles, educational journals, and research reports published in the past five years. The study's findings indicate that strategies such as a writing process-based approach, the use of digital media, formative feedback, collaborative learning, and the integration of real-life contexts into writing assignments have proven effective in increasing student motivation and writing quality. Furthermore, the teacher's role as a facilitator, capable of guiding and providing space for the exploration of ideas, also strengthens students' interest and literacy skills. This study recommends the development of professional training for teachers to enhance their competency in implementing innovative and impactful writing learning strategies. The implications of this study indicate that targeted writing skills not only improve student literacy but also strengthen critical, creative, and reflective thinking skills, which are essential in today's digital age.